Operational Challenges and Strategic Solutions for Power Distribution in Mendol Island - Dalie Priasmoro; Akbar Adhi Utama (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This thesis addresses critical issues within the plant's capacity and operational framework, emphasizing the importance of enhancing the generation system's resilience through the N-1 and N-2 capacity criteria. Methodology/approach: The research methodology encompasses both qualitative and quantitative data collection methods, including observations, interviews, brainstorming sessions, and document reviews. Results/findings: The study reveals a four-year gap between target and actual performance, marked by low energy output and unstable fuel use. Applying N-1 and N-2 criteria is key to maintaining system reliability, especially with renewable energy integration. Conclusions: The Teluk Dalam Diesel Power Plant faces inefficiencies and capacity issues that reduce performance. Applying N-1 and N-2 criteria is essential to improve reliability and ensure long-term operational resilience, especially with renewable energy integration. Limitations: This study is limited by its focus on a single power plant, which may affect the generalizability of its findings to other facilities. Additionally, some operational data relied on internal reports and may be subject to interpretation or lack independent verification. Contribution: This research contributes to power distribution management by analyzing challenges at the Teluk Dalam Diesel Power Plant and offering solutions to improve its performance and sustainability.